Teachers’ Perceptions and Practices in Using ICT for ELT at the Secondary Level - Yonjan, Raju (Journal of NELTA Koshi (JoNK), 2024)
Information and Communication Technology is a daily used material across the globe nowadays which has been recognized to be included in Education field. The study aims at teachers’ perceptions and practices in using ICTs. This study employed a quantitative research design for Data collection among 40 ELT teachers from 9 different rural/municipalities in Sindhuli. The experiences of using different ICT gadgets and digital tools in the ELT were collected using a questionnaire. The findings of the study are that the students seemed eager to learn from the ICT gadgets and digital tools while integrating it into the teaching pedagogies. I report that the ELT teachers have positive experience on using the ICTs. The study further says that 62% teachers are positive towards ICTs usage in the ELT classroom. This study helps the concerned authorities to think about the use of ICT gadgets and digital tools in the ELT classroom. The study recommends that there is a need of a series of training on how to integrate ICTs into the teaching pedagogies.